Case report: Systemic tuberculosis with prostate involvement mimicking prostate cancer with multiple metastases on 18F-FDG and 18F-PSMA PET/CT - Sun, Xinyao; Qiu, Yongkang; Song, Lele; Kang, Lei (Frontiers in Medicine, 2024)
Background Prostate tuberculosis is a common form of urogenital tuberculosis that occurs in men. Clinical and imaging manifestations of prostate tuberculosis are atypical, which often need to be differentiated from benign prostatic hyperplasia, a prostate malignant tumor, and a urinary tract infection. Although prostate-specific membrane antigen (PSMA) is considered a specific biomarker for prostate cancer, it is also found within tuberculosis tissues that may be stimulated by angiogenic factors. An abnormal PSMA uptake on positron emission tomography combined with computed tomography (PET/CT) should eliminate the possibility of tuberculosis. Case report In this study, we reported a case of a 51-year-old man with an elevated erythrocyte sedimentation rate (ESR) but a normal prostate-specific antigen (PSA) value. 2-Deoxy-2-[fluorine-18]-fluoro-D-glucose (18F-FDG) and [fluorine-18]-prostate-specific membrane antigen (18F-PSMA) PET/CT scans were performed for further evaluation. The prostate showed a high fluoro-D-glucose (FDG) uptake but a slight PSMA uptake. Multiple osteolytic bone destruction and lymph nodes with an increased FDG uptake but a mild PSMA uptake were observed throughout the body. Systemic tuberculosis was diagnosed based on the prostate biopsy and the positive result of the T-cell spot test regarding tuberculosis infection. After 6 months of standard anti-tuberculosis treatment, the patient experienced symptom relief. Conclusion In the case of a urinary tract infection, where the prostate shows high FDG uptake lesions with perilesional abscess, a mildly increased PSMA uptake, a low PSA value, a high ESR, and relevant clinical symptoms, tuberculosis should be considered and laboratory tests are required, especially when symptoms are relieved after successful anti-tuberculosis therapy. The final confirmation of the diagnosis still relies on pathological examination.